Ritual Wetu Telu dan makna Spiritualitas Budaya pada Masyarakat Adat Desa Bayan - Destina Runpita Suari; Hariyanto Supriadi; Ananda Desiani Fitri; Reva Kurniawati; Jepri Utomo; Mila Noviana (Peneliti.net, 2026)
The existence of Wetu Telu in Bayan, North Lombok, reflects the close relationship between religion and local culture in Indonesian society. Wetu Telu is not a religion in itself, but rather a cultural and spiritual system that developed through an acculturation process between Islamic teachings and the local traditions of the Sasak people, passed down through generations. However, modernization and the rapid flow of global culture are slowly influencing the younger generation, leading to a decline in understanding of local cultural values ​​and spiritual traditions. Therefore, this study aims to examine the ritual worship patterns practiced by the Wetu Telu community and understand the cultural and spiritual meanings contained within them. This study used a qualitative descriptive approach and was conducted in Bayan Village, North Lombok Regency. Data were collected through interviews, observations, and documentation, involving traditional leaders and the local community. The research results show that Wetu Telu not only represents religious practices but also serves as the cultural identity of the Sasak Bayan people. The